Antimicrobial Properties of Strychnos phaeotricha (Loganiaceae) Liana Bark Secondary Metabolites at the Interface of Nanosilver Particles and Nanoencapsulation by Chitosan Transport Vehicles. (20th May 2022) - Tchangou Njiemou, Armel Florian; Paboudam Gbambie, Awawou; Fannang, Simone Veronique; Vayarai Manaoda, Antoine; Gvilava, Vasily; Spieß, Alex; Fonye Nyuyfoni, Gildas; Mepoubong Kegne, Nelie Alida; Ntoumba, Agnes Antoinette; Belle Ebanda Kedi, Philippe; Enone, Bertin Sone; Ngolsou, Francis; et al.
Abstract : In this study, Strychnos phaeotricha liana bark extract was used as a metabolite container both on the surface of metallic nanosilver and encapsulated by a chitosan polymer. The plant extract was able to reduce Ag + into Ag 0 efficiently, and the encapsulation rate was determined. The synthesized nanoderivatives were characterized using ultraviolet-visible spectrophotometry (UV-Vis), Fourier transform infrared (FTIR) spectroscopy, powder X-ray diffraction (PXRD), scanning electron microscopy (SEM), and energy dispersive X-ray (EDX) spectroscopy. These methods allowed for the determination of grain size, elemental mapping, form, and the presence of secondary metabolites at the interface of the silver. Antimicrobial properties and the oral acute toxicity profile of the generated nanoderivatives were assessed. Overall, the results show plasmon resonance bands 380–550 nm in range and metabolites at the interface of a spherical nanosilver grain of 13.5 nm diameter in size. The hybrid nanosilver and encapsulated chitosan exhibited significant antimicrobial activity against Salmonella spp, Echerichia coli, and Candida spp. Both nanosilver grains and nanocapsules were found to be nontoxic at the tested doses and are potential models to prevent microbial resistance.